PENYULUHAN TENTANG KHASIAT DAUN BANDOTAN TERHADAP PENURUNAN KADAR GULA DARAH DI PUSKESMAS TALUN KENAS - Delisma Simorangkir (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Background: Diabetes mellitus is a metabolic disease with chronic characteristics of hyperglycemia with metabolic disorders of carb, fats, and proteins. Therapies using synthetic drugs require a substantial amount of money and are having these side effects that encourage people to begin shifting into the traditional treatment of bandotan leaves. Purpose: To determine the effectiveness of bandotan leaf ethanol extract can reduce blood sugar levels compared to glibenclamide drugs. Method: The method used is the experimental method. The sample was extracted by maceration method using 70% ethanol sailor. Testing for antidiabetic effects was carried out on 15 male white rats divided into 5 treatment groups, namely the first group negative control (CMC Na 0.5%), the second group positive control (glibenclamide), the third group dose 126 mg / BB Kg, 4th group dose 252 mg / Kg BB, and group 5 dose 378 mg / Kg BB. The results were tested using the ANOVA method. Result: Based on this study, the ethanol extract of bandotan leaves at a dose of 126 mg / Kg BB, 252 mg / Kg, and 378 mg / Kg BB gave a decrease in blood sugar levels. the administration of bandotan leaf extract with a dose of 378 mg / Kg BB gave the same effective results as the glibenclamide drug while the negative control group (CMC Na 0.5%) was not effective in lowering blood sugar levels. Conclusion: Bandotan leaf ethanol extract has the effect of decreasing blood sugar levels which are almost the same as glibenclamide drugs in male white mice induced with alloxan.